Literacy as an Effort to Prevent Bullying in Elementary Schools : A Literature Study - Azizah, Farinka Nurrahmah; Wasino, Wasino; Doyin, Mukh; Bashori, Muzzaki (Proceedings of International Conference on Science, Education, and Technology, 2024)
Bullying is a serious problem that can disrupt the academic and psychosocial development of students in elementary schools. This study aims to explore the role of literacy as an effort to prevent bullying in elementary schools. Literacy in this context includes reading and writing skills, as well as emotional and social literacy that is important for understanding the feelings of others and communicating effectively. This article uses the literature review method or library research, with data collection through the documentation method. Data analysis was conducted using content analysis techniques, which involved repeated reading of the literature and cross-checking between literature to ensure the accuracy of the discussion and prevent misinformation in data analysis. In this discussion, empirical research results and case examples from various countries that demonstrate the effectiveness of literacy programs in reducing bullying incidents in primary schools are presented. The practical implications of these research findings for the development of holistic and integrated literacy programs are also discussed, including prevention and intervention strategies involving teachers, parents and the whole school community.